(untitled) (Medical Forum Monthly, 2022)
Objective: To find the frequency of vitamin D deficiency in patients with chronic liver disease and evaluate the relationship of vitamin D deficiency with advancement in liver disease severity. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Department of Gastroenterology, Lady Reading Hospital, Peshawar from August 2020 to February 2021. Materials and Methods: One hundred and forty one patients with chronic liver disease were enrolled. Vitamin D level was measured in the blood sample of patients in the hospital laboratory. The cut-off value for vitamin D deficiency was set at Serum vitamin D [25 (OH) D] level <30 nmol/L. Results: Ninety nine patients (70.2%) were males and 42 patients (29.8%) were females. The mean age was 53.40±12.19 years. Hepatitis C was the most common underlying cause of chronic liver disease observed in 80 patients (56.7%). 83 patients (58.9%) had Child-Pugh Class C chronic liver disease. Vitamin D deficiency was observed in 95 patients (67.4%). Gender and Child-Pugh Class had a significant association with vitamin D deficiency. Conclusion: Vitamin D deficiency is a frequently occurring finding in patients. Female patients with advanced liver fibrosis are more likely to have vitamin D deficiency.